2022
DOI: 10.3389/fsurg.2022.863287
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Immobilization After Hip Reconstruction in Cerebral Palsy: No Difference Between Hip Spica and Abduction Pillow

Abstract: PurposeThis study aims to compare radiographic outcomes and complication rates of immobilization with an abduction pillow to spica casting for postoperative care after a hip reconstruction with varus derotational proximal femur osteotomy (VDRO) with or without pelvic osteotomy for children with cerebral palsy (CP).Methods233 children (1–18 years old) diagnosed with CP that underwent VDRO with or without pelvic osteotomy were identified, of which 188 patients were immobilized with a spica cast and 45 were immob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 20 Ruzbarsky et al 21 also reported decubitus ulcers in 3/61 (4.9%) and Pisecky et al 22 counted superficial skin lesions in 7/83 (8.4%). When compared spica cast and abduction pillow, Vasconcellos et al 23 reported incidence of pressure sore associated with abduction pillow especially over bony prominences and from pillow straps. In our series, we have had 2/148 (1.3%) rate of skin sores that were managed by tissue viability team and did not need any intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Ruzbarsky et al 21 also reported decubitus ulcers in 3/61 (4.9%) and Pisecky et al 22 counted superficial skin lesions in 7/83 (8.4%). When compared spica cast and abduction pillow, Vasconcellos et al 23 reported incidence of pressure sore associated with abduction pillow especially over bony prominences and from pillow straps. In our series, we have had 2/148 (1.3%) rate of skin sores that were managed by tissue viability team and did not need any intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In their case series, Tabaie et al 31 compared the complication rate of three different types of immobilization after hip reconstruction in CP, namely, hip spica, Petrie cast, and abduction pillow. Likewise, Vasconcellos et al 23 compared hip spica and abduction pillow. They both did not find a significant difference in complication rate between groups and recommended use of less restrictive types of immobilization.…”
Section: Discussionmentioning
confidence: 99%